Immunophenotyping of Paucicellular Samples. Issue 1 (15th February 2018) - Stacchini, Alessandra; Demurtas, Anna; Aliberti, Sabrina
ABSTRACT: Immunophenotyping of paucicellular samples may represent a diagnostic challenge in the flow cytometry (FC) laboratory routine, as the scarcity of cells limits the number of tests that can be performed. Specimens such as fine needle aspirates (FNA), human body fluids (BF), cerebrospinal fluid (CSF), or ocular fluid (OF) sent for FC investigations in the case of suspicion of lymphoma, or for lymphoma monitoring, may contain very low numbers of cells. In these cases, it is mandatory to obtain the largest amount possible of useful information from a single tube. The basic protocol described in this unit provides a method that combines the use of multiple monoclonal antibodies (MAbs) with a Boolean gating strategy to identify and quantify the main lymphocyte populations, as well as to detect lymphomatous B cells or any aberrant T cell expression, if present, in paucicellular samples. Curr. Protoc. Cytom . 68:9.46.1‐9.46.14. © 2014 by John Wiley & Sons, Inc.